2011
DOI: 10.1002/chem.201100768
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Generation and Intramolecular Schmidt Reaction of Keto Azides in a Microwave‐Assisted Flow Format

Abstract: A two-stage synthesis of lactams in flow is described. Thus, a keto alkyl halide is displaced in a microwave-assisted, continuous flow organic synthesis format (MACOS) to generate a reactive alkyl azide. Without isolation, a flowed solution containing this azide is then combined with TFA to afford a lactam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 50 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Notably, keteniminium salts 6 44,45 and ethylene 46 have rarely been used in previous analogous transformations, and, to the best of our knowledge, no examples of their mutual [2+2] cycloaddition have been reported to date. We found that the keteniminium salts 6a and 6b (generated in situ from amides 7a and 7b) reacted with ethylene at 75 °C at atmospheric pressure to give the corresponding cycloadducts, which provided the target ketones 5a and 5b after hydrolysis (Scheme 4).…”
Section: Scheme 2 Strinc Sequencementioning
confidence: 99%
“…Notably, keteniminium salts 6 44,45 and ethylene 46 have rarely been used in previous analogous transformations, and, to the best of our knowledge, no examples of their mutual [2+2] cycloaddition have been reported to date. We found that the keteniminium salts 6a and 6b (generated in situ from amides 7a and 7b) reacted with ethylene at 75 °C at atmospheric pressure to give the corresponding cycloadducts, which provided the target ketones 5a and 5b after hydrolysis (Scheme 4).…”
Section: Scheme 2 Strinc Sequencementioning
confidence: 99%
“…[8] Almost all finechemical manufacturing is done in batch and the assembly of the exhaustive data necessary to make 'go, no-go' decisions about a chemical process is a waste-generating, resource-and labor-intensive exercise that frequently can take several weeks to many months to compile. [9] Flow chemistry can be performed on an infinitely smaller scale than batch making it safer by design [10][11][12][13][14] and larger amounts of material can be obtained by 'scaling out', which means running the process for a prolonged period of time and/or in parallel to produce only that which is required. [15] Novel developments in flow technology can add flexibility to the approach researchers take for the synthesis of important compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Aubéand co-workers integrated the intramolecular Schmidt reaction into a microwave flow-reactor. 22 Inspired by their pioneering work, our research showed that the ketone Schmidt reaction in MsOH−DME system can be performed quickly and safely with minimized amount of azide in a flow manner.…”
Section: ■ Introductionmentioning
confidence: 99%